Impaired Chylomicron Assembly Modifies Hepatic Metabolism Through Bile Acid–Dependent and Transmissible Microbial Adaptations. Issue 4 (23rd May 2019) - Xie, Yan; Matsumoto, Hitoshi; Kennedy, Susan; Newberry, Elizabeth P.; Moritz, William; DeBosch, Brian J.; Moley, Kelle H.; Rubin, Deborah C.; Warner, Brad W.; Kau, Andrew L.; Tarr, Phillip I.; Wylie, Todd N.; et al.
Abstract : The mechanisms by which alterations in intestinal bile acid (BA) metabolism improve systemic glucose tolerance and hepatic metabolic homeostasis are incompletely understood. We examined metabolic adaptations in mice with conditional intestinal deletion of the abetalipoproteinemia (ABL) gene microsomal triglyceride transfer protein ( Mttp‐IKO ), which blocks chylomicron assembly and impairs intestinal lipid transport. Mttp‐IKO mice exhibit improved hepatic glucose metabolism and augmented insulin signaling, without weight loss. These adaptations included decreased BA excretion, increased pool size, altered BA composition, and increased fibroblast growth factor 15 production. Mttp‐IKO mice absorb fructose normally but are protected against dietary fructose‐induced hepatic steatosis, without weight loss or changes in energy expenditure. In addition, Mttp‐IKO mice exhibit altered cecal microbial communities, both at baseline and following fructose feeding, including increased abundance of Bacteroides and Lactobacillus genera. Transplantation of cecal microbiota from chow‐fed Mttp‐IKO mice into antibiotic‐treated wild‐type recipients conferred transmissible protection against fructose‐induced hepatic steatosis in association with a bloom in Akkermansia and increased Clostridium XIVa genera, whose abundance was positively correlated with fecal coprostanol and total neutral sterol excretion in recipient mice. However, antibiotic‐treated Mttp‐IKO mice were still protected against fructose‐induced hepatic steatosis, suggesting that changes in microbiota are not required for this phenotype. Nevertheless, we found increased abundance of fecal Akkermansia from two adult ABL subjects with MTTP mutations compared to their heterozygous parents and within the range noted in six healthy control subjects. Furthermore, Akkermansia abundance across all subjects was positively correlated with fecal coprostanol excretion. Conclusion: The findings collectively suggest multiple adaptive pathways of metabolic regulation following blocked chylomicron assembly, including shifts in BA signaling and altered microbial composition that confer a transmissible phenotype.